Molecular characterisation of side population cells with cancer stem cell-like characteristics in small-cell lung cancer - Salcido, C D (Nature Publishing Group, 2010)
BACKGROUND: Side population (SP) fraction cells, identified by efflux of Hoechst dye, are present in virtually all normal and malignant tissues. The relationship between SP cells, drug resistance and cancer stem cells is poorly understood. Small-cell lung cancer (SCLC) is a highly aggressive human tumour with a 5-year survival rate of <10%. These features suggest enrichment in cancer stem cells. METHODS AND RESULTS: We examined several SCLC cell lines and found that they contain a consistent SP fraction that comprises <1% of the bulk population. Side population cells have higher proliferative capacity in vitro, efficient self-renewal and reduced cell surface expression of neuronal differentiation markers, CD56 and CD90, as compared with non-SP cells. Previous reports indicated that several thousand SP cells from non-small-cell lung cancer are required to form tumours in mice. In contrast, as few as 50 SP cells from H146 and H526 SCLC cell lines rapidly reconstituted tumours. Whereas non-SP cells formed fewer and slower-growing tumours, SP cells over-expressed many genes associated with cancer stem cell and drug resistance: ABCG2, FGF1, IGF1, MYC, SOX1/2, WNT1, as well as genes involved in angiogenesis, Notch and Hedgehog pathways. CONCLUSIONS: Side population cells from SCLC are highly enriched in tumourigenic cells and are characterised by a specific stem cell-associated gene expression signature. This gene signature may be used for development of targeted therapies for this rapidly fatal tumour.